Five‐year mortality of heart failure with preserved, mildly reduced, and reduced ejection fraction in a 4880 Chinese cohort. (18th April 2022) - Chen, Shiqun; Huang, Zhidong; Liang, Yan; Zhao, Xiaoli; Aobuliksimu, Xiemuxikaimaier; Wang, Bo; He, Yibo; Kang, Yu; Huang, Haozhang; Li, Qiang; Yao, Younan; Lu, Xiaozhao; et al.
Abstract: Aims: Available evidence is incomplete and inconsistent in the outcomes of heart failure (HF) patients with preserved ejection fraction (HFpEF), mildly reduced ejection fraction (HFmrEF), and reduced ejection fraction (HFrEF). There are also limited data on the proportions and long‐term prognosis among the three HF phenotypes in China. We aimed to characterize the 5 year prognosis in three HF phenotypes according to EF in a cohort of hospitalized HF patients undergoing coronary angiography in southern China. Methods and results: Hospitalized patients with HF were enrolled from the Cardiorenal ImprovemeNt registry (CIN; ClinicalTrials.gov NCT04407936) between January 2007 and December 2014. HF phenotypes were defined as HFpEF (EF ≥ 50%), HFmrEF (EF 41–49%), and HFrEF (EF ≤ 40%). Kaplan–Meier and Cox proportional hazards models were constructed to examine differences in 5 year outcomes in HF patients with different phenotypes. A total of 4880 HF patients [mean age: 61.8 ± 10.3, male: 3156 (64.7%)] were included: 2768 (57%) had HFpEF, 1015 (21%) had HFmrEF, and 1097 (22%) had HFrEF. Patients with HFrEF were older than those with HFpEF (62.5 ± 10.6 vs. 61.3 ± 10.1, P  < 0.001) and more likely to be male (78.0% vs. 55.9%, P  < 0.001). With 5 year follow‐up through the end of December 2019, 1624 (27.6%) patients died. Controlling confounding variables, declined EF category was independently associated with increased 5 year mortality {HFrEF 25.2% vs. HFpEF 13.4%, adjusted hazard ratio [aHR]: 1.85 [95% confidence interval (CI): 1.45 to 2.35]; HFmrEF 18.1% vs. HFpEF 13.4%, aHR: 1.40 [95% CI: 1.08 to 1.81]; HFrEF 25.2% vs. HFmrEF 18.1%, aHR: 1.32 [95% CI: 1.02 to 1.71]}. Conclusions: In this Chinese cohort, patients with HFrEF account for less than a fourth of HF patients. One‐sixth individuals with HF died in 5 years. HFrEF was associated with a nearly two‐fold increased risk of 5 year mortality than HFpEF. Further studies are needed to prospectively evaluate the efficacy of improving treatment on outcomes in all three HF phenotypes.